If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * 4 + 233 = y Reorder the terms for easier multiplication: 4x + 233 = y Reorder the terms: 233 + 4x = y Solving 233 + 4x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-233' to each side of the equation. 233 + -233 + 4x = -233 + y Combine like terms: 233 + -233 = 0 0 + 4x = -233 + y 4x = -233 + y Divide each side by '4'. x = -58.25 + 0.25y Simplifying x = -58.25 + 0.25y
| -3x-5=34 | | 9v^2+2v-63=8v | | 9v+2v-63=8v | | 2x^3-3x^2-18x-27=0 | | 2cos^2x-coax-1=0 | | 4+2m=-28 | | y+2=-6(x-3) | | 4x+4=4x-12 | | 10n+7=12 | | 1/2x-9=15 | | 4u+16=48 | | -4(8v-3)=-8v+36 | | -13=5x+2 | | x^2-6xy+y^2=6 | | 3x+x+21=-7 | | 3x=-159 | | 4x-7=271 | | x+45+45+35=360 | | 5(x-1)=3x+25 | | 11x+16=93 | | 344/2 | | 5sin(x-5)/4cos(x-5) | | 7x+1=61 | | -5(7+n)=-37-4n | | 4+4x=21x+12 | | (2x+1)sq-6=19 | | 4+49x=21x+12x | | 11x+9=11x-6 | | -11f=7(-1-2f)+5 | | 7x*9-2=5x-6 | | 9h+3=7h+5 | | 300+10x=y |